A Study of Interaction Effect of Financial Performance on the Relationship of Board Gender Diversity and Corporate Social Responsibility - Kumar, Neha; Kumar, Parul; Nigam, Devesh (Prabandhan: Indian Journal of Management, 2021)
Purpose : This paper aimed to investigate the relationship between board diversity, financial performance, and CSR of firms. Along with this, an attempt was made to study the interaction effect of board diversity and financial performance on the CSR spending of the firms. Methodology : Panel data of 80 companies listed on BSE 100 index were taken for the period starting from April 1, 2014 – March 31, 2019. The data pertaining to CSR spending, board characteristics, and financial performance has been taken into consideration. Panel data regression was employed to test the hypotheses framed. Findings : It was concluded that board size, proportion of women directors, and corporate governance played a significant role in impacting the CSR activities of the firms. As the number and proportion of women directors increases, the CSR spending of the firms improves. The return on assets, age, and size of the firms also significantly impacted the CSR spending. Practical Implications : Thus, the major implications of the study are to understand how the mandatory provision related to the appointment of women directors on board influences the financial performance and CSR spending of the firms. This study statistically confirmed that appointing more women on board improved the CSR of the firms. Originality : The present research made an attempt to enrich the existing literature related to CSR, board diversity, and financial performance. With respect to India, very few research studies have worked on examining the relationship among these variables.